Development of HOTS Kinematics Questions with Daily Activities - Suyani, Tutik; Handhika, Jeffry; Sasono, Mislan (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
The ability to think critically and creatively can be the strongest foundation of science. They can be developed by answering HOTS questions. This research aims to develop HOTS Kinematics questions with daily activities. This research employed the 4D model. The CVI value was 0.998, based on content validity, construct, and language validation results. The product trials were held twice to see the consistency of the test results. The first and second product trial results found that 12 questions were valid, with reliability in the first product trial of 0.694 and the second product trial of 0.977. In addition to the validity and reliability tests, the discriminating power test and the difficulty level test were also carried out. The result of the analysis of the research product is that 12 of 30 questions developed were suitable for use, marked by the value of test item validity, reliability, difficulty level test, and discriminating power test, which were consistent with the first and second product trials. The questions were developed to have indicators of critical and creative thinking. Of twelve valid questions, seven are questions with creative thinking indicators, and five items with critical thinking indicators. The product of this development can be used as an instrument to improve critical and creative thinking skills.